Resorts : management and operation - Mill, Robert Christie (Hoboken, N.J. : Wiley, 2012)
"The 3rd Edition of Resorts: Management and Operation is a summary of almost 30 years of thought, analysis, and research into the field of resort management written from a business viewpoint yet takes into account the unique structure of resorts. The text is divided into three sections. Each section has a philosophical basis for the inclusion of the subsequent principles and practices.The first section covers major types of resorts: those that are mountain-based, beach-based and golf/tennis based. Two chapters are devoted to each of the various resort types. The first chapters of each resort type focuses on development issues with the impact on operations noted throughout. The second chapter in each resort type deals with guest profiles and management issues. The second section highlights what makes managing a resort different from managing a 'regular' hotel. The final section features a newly expanded chapter on spas, pools, and indoor water parks along with individual chapters on specialty resorts, cruise ships and casinos, reflecting the importance of these types of properties"--Provided by publisher.
Includes bibliographical references and index.
Tourism
Keywords: Resorts -- Management